Etika Komunikasi Siswa kepada Guru dalam Perspektif Aktivitas Kelompok Remaja Islam di SMA PGII 2 Bandung - Cahya Agung Nugraha; Asep Dudi Suhardini (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. The educational process will run conducive if aspects of communication between students and teachers are harmoniously established. Communication between students and teachers cannot be assessed only in terms of quantity or intensity but rather quality in this case communication ethics. One of the problems faced in the field of education is the decline in ethics of student communication to teachers. Communication ethics is a procedure for someone to convey information that is in accordance with moral values so that they can judge the good or bad behavior of a person. For this reason, a program or forum that accommodates students is needed to actualize themselves and to provide guidance related to religious values in order to improve the quality of students' communication ethics to teachers. The purpose of this study is to find out: 1) How active students are in participating in the KRI; 2) How is the ethics of student communication to the teacher; 3) The effect of the students' activeness in following the KRI on communication ethics to the teacher. This research is a quantitative correlational research approach. The population of this study was students of KRI members with a sample of 42 students. The analysis technique used is a single predictor regression analysis. The results showed that there was no influence between the activeness of students in joining the KRI program with the ethics of student communication to teachers in SMA PGII 2 Bandung. Correlation coefficient value of 0.080 with a significance of 0.069 where p> 0.05. This means that students 'activeness in joining the KRI program has not shown a significant influence on the quality of students' communication ethics to teachers, so the work hypothesis is rejected. Regression test results obtained R-square 0.08 or 8% and the remaining 92% is influenced by variables that have not been revealed in this study. In conclusion, the KRI program has not yet led to an improvement in the quality of students' communication ethics to teachers. This is evidenced from the final assessment of the KRI program which is more oriented towards students' cognitive aspects in Islamic insight and vision and mission which are still normative and has not led to an increase in the quality of students' communication ethics to teacher. Abstrak. Proses pendidikan akan berjalan dengan kondusif jika aspek komunikasi antar siswa dengan guru terjalin secara harmonis. Komunikasi antar siswa dengan guru tidak dapat diniliai hanya dari segi kuantitas atau intensitas melainkan kualitas dalam hal ini etika komunikasi. Salah satu masalah yang dihadapi dalam bidang pendidikan yaitu adanya penurunan etika komunikasi siswa kepada guru. Etika komunikasi adalah tata cara seseorang dalam menyampaikan informasi yang sesuai dengan nilai moral sehingga dapat menilai baik atau buruk perilaku seseorang. Untuk itu dibutuhkan program atau wadah yang menampung para siswa dalam mengaktualisasikan diri serta dalam memberikan pengarahan terkait nilai-nilai keagamaan guna meningkatkan kualitas etika komunikasi siswa kepada guru. Tujuan dari penelitian ini adalah untuk mengetahui: 1) Bagaimana keaktifan siswa dalam mengikuti KRI; 2) Bagaimana etika komunikasi siswa kepada guru; 3) Pengaruh keaktifan siswa dalam mengikuti KRI terhadap etika komunikasi kepada guru. Penelitian ini merupakan penelitian dengan pendekatan kuantitatif korelasional. Populasi penelitian ini adalah siswa anggota KRI dengan sampel 42 siswa. Teknik analisis yang digunakan adalah analisis regresi satu prediktor. Hasil penelitian menunjukan bahwa tidak terdapat pengaruh antara keaktifan siswa dalam mengikuti program KRI dengan etika komunikasi siswa kepada guru di SMA PGII 2 Bandung. Nilai koefisien korelasi sebesar 0,080 dengan signifikansi sebesar 0,069 dimana p > 0,05. Hal ini berarti keaktifan siswa dalam mengikuti program KRI belum menunjukan pengaruh yang signifikan terhadap kualitas etika komunikasi siswa kepada guru, sehingga hipotesis kerja ditolak. Hasil uji regresi diperoleh R-square 0,08 atau sebesar 8% dan sisanya 92 % dipengaruhi oleh variabel yang belum terungkap dalam penelitian ini. Kesimpulannya program KRI masih belum mengarah kepada peningkatan kualitas etika komunikasi siswa kepada guru hal ini dibuktikan dari penilaian akhir tentang program KRI yang lebih berorientasi pada aspek kognitif siswa dalam wawasan keislaman serta visi dan misi yang masih normative dan belum mengarah kepada peningkatan kualitas etika komunikasi siswa kepada guru.